Permainan bahasa dalam penggunaan bahasa Inggris oleh pedagang asongan di pantai Kuta Lombok - Nurhandini, Hilmi; Sulistyowati, Sulistyowati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
The playfulness of English is the result of language interference, which can be a source of creating new English variations. The purpose of this study is to describe the form of English playfulness by hawkers at Kuta Beach, Lombok, and the factors of English playfulness. The method is descriptive qualitative. The data collection by ‘simak libat cakap’ or involved conversation observation technique, recording, and taking notes technique. The data analysis method is reduction, presentation, and conclusion. Data analysis shows that the playfulness of English by hawkers comes from loan translation in the form of reduplication of Indonesian and Sasak words into English. There are two forms of loan translation: a change in the meaning of English in accordance with Sasak and Indonesian, and not experiencing a change in meaning but experiencing the addition of English meaning in accordance with Sasak and Indonesian. The factors causing the English playfulness are internal factors such as the difference in vocabulary structure from Sasak and Indonesian to English and the influence of Indonesian and Sasak as the dominant language. Factors external the language are influential in English playfulness, such as level of education, economic status, occupation, regional origin, and the situation of speech.